Genome‐wide association study follow‐up identifies cyclin A2 as a regulator of the transition through cytokinesis during terminal erythropoiesis. Issue 5 (5th February 2015) - Ludwig, Leif S.; Cho, Hyunjii; Wakabayashi, Aoi; Eng, Jennifer C.; Ulirsch, Jacob C.; Fleming, Mark D.; Lodish, Harvey F.; Sankaran, Vijay G.
<x xml:space="preserve">Abstract</x> Genome‐wide association studies (GWAS) hold tremendous promise to improve our understanding of human biology. Recent GWAS have revealed over 75 loci associated with erythroid traits, including the 4q27 locus that is associated with red blood cell size (mean corpuscular volume). The close linkage disequilibrium block at this locus harbors the CCNA2 gene that encodes cyclin A2. CCNA2 mRNA is highly expressed in human and murine erythroid progenitor cells and regulated by the essential erythroid transcription factor GATA1. To understand the role of cyclin A2 in erythropoiesis, we have reduced expression of this gene using short hairpin RNAs in a primary murine erythroid culture system. We demonstrate that cyclin A2 levels affect erythroid cell size by regulating the passage through cytokinesis during the final cell division of terminal erythropoiesis. Our study provides new insight into cell cycle regulation during terminal erythropoiesis and more generally illustrates the value of functional GWAS follow‐up to gain mechanistic insight into hematopoiesis.Am. J. Hematol. 90:386–391, 2015. © 2015 Wiley Periodicals, Inc.